Ab-initio Modeling of Functionalized 2D-Stanene nanostructure in context of FET based Toxic Gas Sensor. Issue 1 (July 2021) - Verma, Swati; Kumar, Arun; Kumar, Hemant; Baghel, Rahul; Pinjarkar, Latika; Verma, Mohan L
Abstract: Detecting toxic gases in the environment cannot be minimized in today's highly polluted world and the reality of global warming. Carbon monoxide is a highly toxic air pollutant and can cause serious health problems. Sensing materials plays a critical role in the performance of gas sensors. Nanostructure materials exhibit better performance as sensing channels in application for developing novel FET-based sensing devices. In the proposed work, the ab-initio study is performed to explore the performance of 2D-Stanene nano sheet as a sensing substrate for application of field-effect transistors as gas sensor. We explored CO gas-adsorption behaviour on pristine, hole-defective, and Pt-doped Stanene sheet and analyzed structural, charge-density, electronic and transport properties by first principles calculations and exploit its potential for high-performance gas sensing. Here in, to get the measure of sensing properties of Stanene nano sheet after the adsorption of gas molecule, first the molecular model of all the adsorption cases are modelled by considering all possible anchoring sites and optimized, and then calculations were performed based on density functional theory (DFT).